2015
DOI: 10.3174/ajnr.a4281
|View full text |Cite
|
Sign up to set email alerts
|

Use of Standardized Uptake Value Ratios Decreases Interreader Variability of [18F] Florbetapir PET Brain Scan Interpretation

Abstract: BACKGROUND AND PURPOSE:Fluorine-18 florbetapir is a recently developed ␤-amyloid plaque positron-emission tomography imaging agent with high sensitivity, specificity, and accuracy in the detection of moderate-to-frequent cerebral cortical ␤-amyloid plaque. However, the FDA has expressed concerns about the consistency of interpretation of [18 F] florbetapir PET brain scans. We hypothesized

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 38 publications
(68 reference statements)
7
30
0
Order By: Relevance
“…These data support our hypothesis that augmenting visual interpretation of amyloid-β PET scans of cognitively normal participants with quantitative information decreased the variability of rater interpretations, which is consistent with other recent studies utilizing a similar Visual Read only technique (Kappa 0.40–0.89) [6, 8–10, 1213, 1718]. Our results also suggest that the addition of quantitative PET scan data is most important for the improved detection of early plaque deposition or in cases where the patient demonstrates borderline Visual or Quantitative Reads (e.g., 1–2 qualitative and/or quantitative positive ROIs).…”
Section: Discussionsupporting
confidence: 92%
“…These data support our hypothesis that augmenting visual interpretation of amyloid-β PET scans of cognitively normal participants with quantitative information decreased the variability of rater interpretations, which is consistent with other recent studies utilizing a similar Visual Read only technique (Kappa 0.40–0.89) [6, 8–10, 1213, 1718]. Our results also suggest that the addition of quantitative PET scan data is most important for the improved detection of early plaque deposition or in cases where the patient demonstrates borderline Visual or Quantitative Reads (e.g., 1–2 qualitative and/or quantitative positive ROIs).…”
Section: Discussionsupporting
confidence: 92%
“…The reported gain of visual read accuracy by taking SUVrs into consideration is also in accordance with the fact that visual read and SUVr results might differ within at least some amyloid PET cases [17][18][19]. Also in accordance with the Pontecorvo et al data, it was recently shown that taking SUVrs into account decreases inter-reader variability of amyloid PET diagnosis [20]. It would be useful to better understand in the present study the discordance between visual and quantitative assessments, and in what settings this occurred.…”
supporting
confidence: 73%
“…In spite of these potential issues, only one study to date has evaluated the performance of quantitative software as an adjunct to visual interpretation. Specifically, Nayate et al [21] recently reported that the use of Siemens Scenium software to quantitate florbetapir PET scans significantly increased interreader reliability. Although an increase in interreader reliability is encouraging, it does not necessarily mean that there has been an increase in reader accuracy.…”
Section: Introductionmentioning
confidence: 99%